Do gene à proteína: explorando o GenBank com alunos do ensino médio - Rosa, Rosane Teresinha Nascimento da (2011)
This study reports on the use of the Didactic Unit (DU): Exploring the GenBank with high school students, which involved 20 school hours with a group of 06 volunteer students from the 2nd year of high school at the Military School of Santa Maria - CMSM/RS, during the 2nd semester of 2009. The aforementioned Didactic Unit was developed in the afternoon, whereas the regular school classes took place in the morning period. The DU was structured according to the Three Pedagogic Moments (3PM) proposed by Delizoicov and Angotti (1994), that is: Initial Problematization (IP), Knowledge Organization (KO) and Knowledge Application (KA). The DU included theoretical and practical classes on proteins and protein synthesis and monitored access to the NCBI (National Center Biotechnology Information), using the links OMIM and Entrez Gene. The aim of this DU was to identify whether students achieved better understanding of the relation DNA-RNAprotein, using the NCBI tools aforementioned. In order to evaluate the students performance, conceptual maps based on the score table proposed by Novak and Gowin (1996) were used, as well as individual interviews and analysis of the tests given to the students. The reference conceptual map had 52 points; two students scored 41 and one student scored 26 points, respectively. In the quantitative and the qualitative analyses, it was possible to identify a significant improvement in the conceptual relations of these students about the protein synthesis. The data suggests that the access to the GenBank, which was used as a didactic strategy in the Unit, afforded this improvement. In the students interviews, difficulties concerning the fluency in English were mentioned, which were overcome by using online translators, associated to the English classes that the students have in the Military School. Also, students evaluated positively the opportunity for learning to use new technologies. In the post-test, it was verified an improvement in the scores related to protein and protein synthesis. Finally, it can be inferred that for the small group of students who participated in this study, the experience was of a great value.